2020
DOI: 10.3390/nu12092615
|View full text |Cite
|
Sign up to set email alerts
|

24-h Urine Collection: A Relevant Tool in CKD Nutrition Evaluation

Abstract: Dietary management is a cornerstone of Chronic Kidney Disease (CKD) monitoring, and dietary surveys often difficult to perform. We studied in a CKD patient cohort with two years follow-up, whether validated 24-h urine ionogram would be a relevant tool for diet evaluation and compliance. We included 404 non-dialysis CKD patients, with three evaluations, including repeated measurements of fractional renal creatinine clearance and 24-h urine collection. Completeness of the 24-h urine collection, assessed by daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…A total of 4 aliquots of 2 mL were stored at -80°C, out of which one was given to the biochemistry laboratory for analysis. Estimation of dietary intake using 24-h urinary excretion has been considered a reliable tool provided the compliance of 24-h urine collection has been validated which we have done carefully ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4 aliquots of 2 mL were stored at -80°C, out of which one was given to the biochemistry laboratory for analysis. Estimation of dietary intake using 24-h urinary excretion has been considered a reliable tool provided the compliance of 24-h urine collection has been validated which we have done carefully ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dietary protein intake is best estimated by measuring the urea nitrogen appearance rate, which requires a 24-h urine collection (22). Similarly, the estimation of the 24-h urinary sodium excretion is the gold standard for estimating salt intake (23)(24)(25)(26), and dietary potassium intake is correlated with the 24-h urinary excretion of potassium (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating nutritional intake and dietary monitoring is of utmost importance for providing proper nutritional counselling. Abdel-Nabey et al, on behalf of the French NephroTest Study Group, studied over 400 CKD patients and concluded that twenty-four-hour urine collections are feasible and represent a reliable tool for dietary monitoring and could be used in making individual recommendations for salt and protein intake [ 8 ]. Expanding on the topic of assessing nutritional parameters, Ginos and Olde-Engberink reviewed evidence on sodium and potassium intake methods based on twenty-four-hour urine collections or spot urine estimations (including spot Na/K ratio) in the general population and CKD patients, exploring suggestions that may improve test accuracy without increasing the associated burden for the patients [ 9 ].…”
mentioning
confidence: 99%